2009
DOI: 10.1111/j.1468-2982.2009.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Premonitory Symptoms in Paediatric Migraine: A Questionnaire Study in 103 Children and Adolescents

Abstract: The prevalence and characterization of premonitory symptoms have not been rigorously studied in children and adolescents. Using a questionnaire, we retrospectively studied the prevalence of 15 predefined premonitory symptoms in a clinic-based population. In 103 children and adolescents fulfilling the International Classification of Headache Disorders, 2nd edn criteria for paediatric migraine, at least one premonitory symptom was reported by 69 (67%). The most frequently reported premonitory symptoms were face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 15 publications
5
88
2
1
Order By: Relevance
“…Two authors (SG and GB) read the title and abstract of every identified study and critically appraised the full text of potentially eligible studies. Table 1 summarizes the studies of prodrome reported in children and adults with migraines [4][5][6][7][8][9][10][11]. Our search reveals no devoted studies to the diagnostic and therapeutic significance of preictal symptomatology in migraines.…”
Section: Methods Literature Searchmentioning
confidence: 99%
“…Two authors (SG and GB) read the title and abstract of every identified study and critically appraised the full text of potentially eligible studies. Table 1 summarizes the studies of prodrome reported in children and adults with migraines [4][5][6][7][8][9][10][11]. Our search reveals no devoted studies to the diagnostic and therapeutic significance of preictal symptomatology in migraines.…”
Section: Methods Literature Searchmentioning
confidence: 99%
“…[8][9][10][11][12][13] In addition, the majority of the studies performed so far have only looked at symptoms starting before the prevalence rates of 9-88%. 3,[8][9][10][11][12][13][14][15][16][17][18] See Table 1 for a breakdown of studies to date in the literature looking at premonitory symptom prevalence.…”
Section: Prevalence Of Premonitory-like Symptoms In Migrainementioning
confidence: 99%
“…17,18 One of these showed a prevalence of 67% in the cohort of 103 children and adolescents with migraine. 18 The other study preselected patients who had reported at least one premonitory symptom.…”
Section: Prevalence Of Premonitory-like Symptoms In Migrainementioning
confidence: 99%
See 2 more Smart Citations